Comparative study on drug safety surveillance between medical students of Malaysia and Nigeria - Abubakar, Abdullahi Rabiu (Ther Clin Risk Manag, 2015)
BACKGROUND: Internationally, there is a remarkable achievement in the areas of drug discovery, drug design, and clinical trials. New and efficient drug formulation techniques are widely available which have led to success in treatment of several diseases. Despite these achievements, large number of patients continue to experience adverse drug reactions (ADRs), and majority of them are yet to be on record. OBJECTIVES: The purpose of this survey is to compare knowledge, attitude, and practice with respect to ADRs and pharmacovigilance (PV) between medical students of Malaysia and Nigeria and to determine if there is a relationship between their knowledge and practice. METHOD: A cross-sectional, questionnaire-based survey involving year IV and year V medical students of the Department of Medicine, Universiti Sultan Zainal Abidin and Bayero University Kano was carried out. The questionnaire which comprised 25 questions on knowledge, attitude, and practice was adopted, modified, validated, and administered to them. The response was analyzed using SPSS version 20. RESULTS: The response rate from each country was 74%. There was a statistically significant difference in mean knowledge and practice score on ADRs and PV between medical students of Malaysia and Nigeria, both at P<0.000. No significance difference in attitude was observed at P=0.389. Also, a statistically significant relationship was recorded between their knowledge and practice (r=0.229, P=0.001), although the relationship was weak. CONCLUSION: Nigerian medical students have better knowledge and practice than those of Malaysia, although they need improvement. Imparting knowledge of ADRs and PV among medical students will upgrade their practice and enhance health care delivery services in the future.